2022
DOI: 10.1001/jamapsychiatry.2022.3255
|View full text |Cite|
|
Sign up to set email alerts
|

Efficacy of Adjunctive D-Cycloserine to Intermittent Theta-Burst Stimulation for Major Depressive Disorder

Abstract: ImportanceThe antidepressant effects of transcranial magnetic stimulation protocols for major depressive disorder (MDD) are thought to depend on synaptic plasticity. The theta-burst stimulation (TBS) protocol synaptic plasticity is known to be N-methyl-D-aspartate (NMDA)–receptor dependent, yet it is unknown whether enhancing NMDA-receptor signaling improves treatment outcomes in MDD.ObjectiveTo test whether low doses of the NMDA-receptor partial-agonist, D-cycloserine, would enhance intermittent TBS (iTBS) tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…Extensive motor practice in M&As incorporates the long-term effects of increased learning, which is known to be subserved by NMDA-receptor dependent LTP (Whitlock et al, 2006;Brown et al, 2021). The applicability of these results outside of the motor cortex and healthy subjects has been supported by Cole and colleagues who found that DCS was sufficient to enhance both motor physiology (Cole et al, 2021), and clinical outcomes in depressed patients (Cole et al, 2022).…”
Section: Discussionmentioning
confidence: 91%
“…Extensive motor practice in M&As incorporates the long-term effects of increased learning, which is known to be subserved by NMDA-receptor dependent LTP (Whitlock et al, 2006;Brown et al, 2021). The applicability of these results outside of the motor cortex and healthy subjects has been supported by Cole and colleagues who found that DCS was sufficient to enhance both motor physiology (Cole et al, 2021), and clinical outcomes in depressed patients (Cole et al, 2022).…”
Section: Discussionmentioning
confidence: 91%
“…A similar combinatorial approach using TMSpharmacologic augmentation of synaptic plasticity with D-cylcoserine (a partial N-methyl-D-aspartate agonist) recently demonstrated increased response rates in patients with depression. 62 Pairing plastogenic agents with brain stimulation may also help non-invasive stimulation overcome the high relapse rates currently limiting these interventions from making a larger clinical impact.…”
Section: Discussionmentioning
confidence: 99%
“…Heightened glutamatemediated learning of contextual cues, drug-cue associations, and glutamate-mediated reward processing in females would contribute to more rapid acquisition and severity of drug dependence in females compared to males. In the context of MDD, our ndings advance Glu as a novel treatment target for medication and adjunctive treatment for positive emotion recovery(Cole et al, 2022).…”
mentioning
confidence: 82%